Three-dimensional volumetric muscle reconstruction of the Australopithecus afarensis pelvis and limb, with estimations of limb leverage - Ashleigh L. A. Wiseman (Royal Society Open Science, 2023)
To understand how an extinct species may have moved, we first need to reconstruct the missing soft tissues of the skeleton, which rarely preserve, with an understanding of segmental volume and muscular composition within the body. The Australopithecus afarensis specimen AL 288-1 is one of the most complete hominin skeletons. Despite 40+ years of research, the frequency and efficiency of bipedal movement in this specimen is still debated. Here, 36 muscles of the pelvis and lower limb were reconstructed using three-dimensional polygonal modelling, guided by imaging scan data and muscle scarring. Reconstructed muscle masses and configurations guided musculoskeletal modelling of the lower limb in comparison with a modern human. Results show that the moment arms of both species were comparable, hinting towards similar limb functionality. Moving forward, the polygonal muscle modelling approach has demonstrated promise for reconstructing the soft tissues of hominins and providing information on muscle configuration and space filling. This method demonstrates that volumetric reconstructions are required to know where space must be occupied by muscles and thus where lines of action might not be feasible due to interference with another muscle. This approach is effective for reconstructing muscle volumes in extinct hominins for which musculature is unknown.